Melanoma of the lower female genital tract (vulva, vagina, and cervix): literature review and own cases - K. V. Safronova; A. S. Artemyeva; A. A. Sidoruk; D. A. Chuglova; K. E. Khidishyan; N. A. Mikaya; I. V. Berlev; A. F. Urmancheeva; E. A. Ulrikh (ABV-press, 2019)
The article covers various aspects of clinical manifestations, diagnosis, and treatment of vulvar, vaginal, and cervical melanomas.